RELEVANSI KURIKULUM PENDIDIKAN TEKNIK BANGUNAN UNJ TERHADAP KOMPETENSI SMK DESAIN PEMODELAN DAN INFORMASI BANGUNAN - Fraharyani, Febby; Murtinugraha, R. Eka; Daryati (Jurnal Penelitian Kebijakan Pendidikan, 2022)
This study aims to determine the level of relevance between the Building Engineering Education study program curriculum in the State University of Jakarta (UNJ), and the competency of Building Design and Information Modeling expertise program in Vocational High Schools (SMK) in ”Kurikulum Merdeka” (Emancipated Curriculum). The objects of the study are the Kurikulum Merdeka guidelines, Semester Lesson Plan for the Building Engineering Education study program, and document on Learning Outcomes for the Building Design and Information Modeling expertise program. The method used in this research was descriptive quantitative. The data were collected through literature review, documentation, and interviews. The data were analyzed by assessing the percentage of each competency or learning element in the expertise program. Then, the results were categorized according to the relevance level, which were divided into very relevant, quite relevant, and irrelevant. The result found that overall; the curriculum of the Building Engineering Education study program is very relevant to the competency of Building Design and Information Modeling expertise program with a correlation of 80.77%.